El requint como instrumento orgánico del pasillo y pasacalle - Merino Padrón, Pablo Esteban (2021)
The miscegenation in America strongly influenced the musical culture of the conquered peoples, including Ecuador. This inherency resulted in new mixedrace rhythms such as Pasillo and Pasacalle, which adopted the requinto as their emblematic musical instrument…